2019
DOI: 10.1002/mabi.201900147
|View full text |Cite
|
Sign up to set email alerts
|

Electroactive Composite of FeCl3‐Doped P3HT/PLGA with Adjustable Electrical Conductivity for Potential Application in Neural Tissue Engineering

Abstract: Conducting polymers (CPs) is one of intelligent biomaterials with the specific properties of reversible redox states, which have a significant effects on the cell behaviors and nerve tissue regeneration. However, the effects of CPs with different electrical conductivity on the behaviors of nerve cells are rarely reported. Therefore, a kind of Poly(3‐hexylthiophene) (P3HT) with certain molecular weight is synthesized by Kumada catalyst transfer polymerization (KCTP) method and employed to prepare bioabsorbable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…These outcomes are achieved due to the fact that electroactive materials are able to create varying surface charges in the material, when mechanical stress is applied, not only acting passively in the body but also providing the appropriate environment to assist, promote or induce specific cellular responses [15,18]. Other electroactive materials such as polylactic acid (PLLA) [19], poly (lactic-co-glycolic acid) (PLGA) [20] and natural polymers such as silk [21] have also been applied for such purposes.…”
Section: Introductionmentioning
confidence: 99%
“…These outcomes are achieved due to the fact that electroactive materials are able to create varying surface charges in the material, when mechanical stress is applied, not only acting passively in the body but also providing the appropriate environment to assist, promote or induce specific cellular responses [15,18]. Other electroactive materials such as polylactic acid (PLLA) [19], poly (lactic-co-glycolic acid) (PLGA) [20] and natural polymers such as silk [21] have also been applied for such purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Although there was no unified conclusion about what level of the electrical conductivity was needed for application in neural regeneration, some ranges of conductivity were reported to be suitable for neural tissue engineering. For instance, Zhang et al 13 found that the P3HT/ PLGA composite with conductivity up to 10 −2 S/ cm could promote the synaptic length over 40 µm. In another study, the polymer hydrogels cross-linked and doped by tannic acid, which exhibited a conductivity (0.05-0.18 S/cm), could accelerate the differentiation of neural stem cells into neurons.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that the PC12 cells displayed better adhesion and spreading on the substrates with higher conductivity. 13 Therefore, it was needed to improve the electrical conductivity of the PPY hybrids.…”
Section: Introductionmentioning
confidence: 99%
“…The increased conductivities up to 10 −2 S/cm promoted the synaptic length over 40 µm, enhancing possible applications on nerve repair. Indeed, by fine tuning the conductivity of the composite, it can promote the high expression of Synapsin 1 (SYN1) and microtubule-associated protein 2 (MAP2), which is an important aspect in nerve repair and regeneration [ 79 ].…”
Section: Applicationsmentioning
confidence: 99%